(untitled) (Bangladesh Journal of Medical Science, 2014)
The terminology Erosio blastomycetica interdigitale is used to describe a clinical entity characterized by erosions disposed interdigitalis on the hands and /or feet, in persons with poor controlled diabetes mellitus, the agent incriminated being Candida Albicans. DOI: http://dx.doi.org/10.3329/bjms.v13i1.16623 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 105-106